Giada De Laurentiis's Recipe for adventure : Naples! - De Laurentiis, Giada (De Laurentiis, Giada. Giada De Laurentiis's recipe for adventure., 2013)
"When their great-aunt comes to live with Alfie and his older sister Emilia, they learn that food can not only take you places but also bring you back home. In the first book in the series, Alfie and Emilia find themselves magically transported to Naples"--